Nanoparticle interactions with live cells: Quantitative fluorescence microscopy of nanoparticle size effects - Shang, Li; Nienhaus, Karin; Jiang, Xiue; Yang, Linxiao; Landfester, Katharina; Mailänder, Volker; Simmet, Thomas; Nienhaus, G. Ulrich (Beilstein Journal of Nanotechnology, 2014)
Engineered nanomaterials are known to enter human cells, often via active endocytosis. Mechanistic details of the interactions between nanoparticles (NPs) with cells are still not well enough understood. NP size is a key parameter that controls the endocytic mechanism and affects the cellular uptake yield. Therefore, we have systematically analyzed the cellular uptake of fluorescent NPs in the size range of 3.3–100 nm (diameter) by live cells. By using spinning disk confocal microscopy in combination with quantitative image analysis, we studied the time courses of NP association with the cell membrane and subsequent internalization. NPs with diameters of less than 10 nm were observed to accumulate at the plasma membrane before being internalized by the cells. In contrast, larger NPs (100 nm) were directly internalized without prior accumulation at the plasma membrane, regardless of their surface charges. We attribute this distinct size dependence to the requirement of a sufficiently strong local interaction of the NPs with the endocytic machinery in order to trigger the subsequent internalization.
Keywords: cell membrane; endocytosis; fluorescence microscopy; nanoparticle; size effect